Urban Land Ownership Study - Urban Land Ownership In Peninsular Malaysia: A Proposed Study - Evers, H.; Goh, Ban Lee; Ratnam, K.J. (USM, 1975)
There has been a common tendency, among academicians and administrators alike, to assume that problems of land tenure are of special significance only in rural areas and therefore worthy of inquiry only in that context.